Middle School: Ultimate Showdown: (Middle School 5) - James Patterson (London : Young Arrow, 2015)
The Khatchadorian kids are an opinionated duo, and as readers of the Middle School stories know, they don't exactly see eye to eye. But when wild-card Rafe and mostly-straight-laced Georgia go at it, the only thing more fun than their ranting is getting to join in! Their back-and-forth banter on a range of topics - from bullying to cafeteria food to school dress codes - introduces more than 40 writing and drawing prompts and other games, along with room for readers to share their own points of view. (Includes over 200 illustrations.)